Analisis Pengaruh Soiling Loss Terhadap Performance Ratio (PR) Setiap String Pada Array Box 114 Di PLTS 7 MWp - Mu'minin, Amirul; Sultan (Depertment of Electrical Engineering University of Mataram, 2025)
The demand for electricity in Indonesia continues to increase, while dependence on fossil fuels poses significant environmental impacts. Solar energy offers a strategic solution, as the country benefits from high solar irradiation throughout the year. One of the factors affecting the performance of Solar Power Plants (PLTS) is soiling loss, which refers to the reduction of energy output due to dust accumulation on photovoltaic (PV) module surfaces. This study was conducted at a 7 MWp PLTS through field observations and mathematical calculations to analyze the influence of soiling loss on performance ratio (PR). The results showed that soiling loss ranged from 2.37% to 28.68%, with PR values varying between 87.20% and 61.97%. Graphical analysis revealed a negative correlation, where higher soiling loss corresponds to lower PR values. Therefore, effective maintenance strategies, such as routine module cleaning based on monitoring data and the application of anti-soiling technologies, are essential to maintain the efficiency and reliability of PLTS operations.